DETERMINAN KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG DAN KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Irwan Hadiwijaya; Khairina Nur Izzaty (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
This study aims to analyze the effect of profitability, solvency, audit opinion, and auditor quality on the timeliness of financial reporting in consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. Secondary data were obtained from 144 annual financial report observations. A quantitative approach was employed using logistic regression analysis with IBM SPSS Version 26. The results showed that auditor quality has a significant positive effect on the timeliness of financial reporting, with an Exp(B) value of 3.703, indicating that companies audited by Big Four firms are 3.7 times more likely to report on time. Meanwhile, profitability, solvency, and audit opinion showed no significant effect. The Nagelkerke R Square value of 0.222 indicates that the four independent variables explain 22.2% of the variability in reporting timeliness. These findings suggest that selecting a high-quality auditor is a more effective strategy for improving reporting timeliness than relying on internal financial indicators or audit opinion types.